Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40463-018-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

In-office laryngeal procedures (IOLP) in Canada: current safety practices and procedural care

Abstract: BackgroundThe advent of chip tip technology combined with advanced endoscopy has revolutionized the field of laryngology in the past decade. Procedures such as transnasal esophagoscopy, site-specific steroid injections, injection laryngoplasty and laryngeal laser treatment can now be performed in the office setting under local anaesthesia. Although In-Office Laryngeal Procedures (IOLPs) have become standard-of-care in many American and several Canadian centers, there are no guidelines regulating the practice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In contrast, the majority answered that they would elect to temporarily discontinue use of warfarin (12/15; 80.0%) or clopidogrel (10/15; 66.7%) during the perioperative period. 16 The decision whether to continue direct oral anticoagulants such as dabigatran was the most polarizing, and perhaps related to decreased familiarity with such agents; 8/15 (53.5%) of those surveyed would choose to continue patients on these medications. 16 Despite these variations in clinical practice, a few small studies have suggested that preoperative discontinuation of antiplatelet and anticoagulation therapy may not be required for certain laryngology procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the majority answered that they would elect to temporarily discontinue use of warfarin (12/15; 80.0%) or clopidogrel (10/15; 66.7%) during the perioperative period. 16 The decision whether to continue direct oral anticoagulants such as dabigatran was the most polarizing, and perhaps related to decreased familiarity with such agents; 8/15 (53.5%) of those surveyed would choose to continue patients on these medications. 16 Despite these variations in clinical practice, a few small studies have suggested that preoperative discontinuation of antiplatelet and anticoagulation therapy may not be required for certain laryngology procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Performing procedures in the office instead of the operating room provides cost and time advantages and avoids general anesthesia, but success and patient-perceived quality through pain control and comfort depend on the provision of appropriate analgesia. [1][2][3]7,8 Accurate and relevant pain assessment is a critical initial step in successful pain control, but studies of postoperative pain have shown that these assessments are often woefully lacking. 12,101,102 In the era of quality-driven metrics and reimbursement, an important contributor is pain measurement, which has been shown to improve self-reported patient satisfaction and HCAHPS scores.…”
Section: Discussionmentioning
confidence: 99%
“…n-office or office-based procedures are common throughout the field of otolaryngology. [1][2][3] They possess advantages of convenience, cost, and efficiency over procedures performed in the operating room. [1][2][3] Improved technology has ensured in-office procedures are safe and effective.…”
mentioning
confidence: 99%
See 2 more Smart Citations